WORKING GROUP OF THE YOUNG CARDIOLOGISTS HAS BEEN ESTABLISHED AT THE SOCIETY OF CARDIOLOGY OF THE RUSSIAN FEDERATION (Столичная издательская компания, 2016)
Working group of the Young Cardiologists has been established at the Society of Cardiology of the Russian Federation.